Teaching English Using podcasts (British Journal of Multidisciplinary and Advanced Studies, 2023)
The paper shows a new method of improving listening skills through podcasts. According to the experiment made at Caucasus International University, Georgia and the project completed in Denver, Colorado USA (Bridge Education Group) it became obvious that a student creating their own podcast is getting increasingly motivated to take their listening skills to the next level. The feedback of the activity showed that before making a podcast a student can be given some vocabulary for building their story or they can search for the vocabulary themselves. In both case they have to create a plot. The process takes a lot time energy and a great many procedures. The final step demonstrated that the experiment should be introduced into the teaching plans on a regular basis.